The Effects Of Intellectual Capital And Innovation On Smes Export Performance In Pakistan The Mediating Role Of Competitive Advantages - Muhammad, Sohail Ayaz (2024)
The export performance of Small and Medium Enterprises (SMEs) has emerged as a focal point of research and policymaking, given its substantial contribution to the economies of developing nations. Among these, Pakistan stands out as a developing country grappling with a decline in export performance, a trend with potential repercussions for both individual firm profitability and the broader economic growth of the nation. This necessitates a thorough investigation into the factors that can bolster the export performance of SMEs in Pakistan. This study presents a comprehensive examination of the factors influencing the export growth of SMEs in Pakistan, with a specific focus on intellectual capital (human, structural, and relational capital), organizational innovation, and competitive advantage. The study's methodology involved the distribution of questionnaires to SME entrepreneurs to gather quantitative data. Data analysis was performed using Statistical Package for the Social Sciences (SPSS) version 25 and Partial Least Squares (PLS). Results indicate that organizational innovation and IC positively impact the export performance of SMEs, both directly and indirectly, through the mediating effect of competitive advantage. Furthermore, competitive advantage is crucial in mediating the relationship between organizational innovation, SME export performance, human capital, structural capital, and relational capital. Despite certain limitations, this study successfully achieved its objectives.